Study on the key influencing factors of reverse flow in U-tube steam generator under natural circulation. (15th June 2022) - Wang, Tianshi; Wang, Yuxuan; Zhao, Pengcheng; Ran, Yiling; Liu, Zijing; Zhu, Enping
Highlights: A three-dimensional CFD model of an inverted U-tube steam generator is established. The sensitivity analysis of several design parameters and operation parameters of steam generator are carried out. The influence mechanism of each influencing factor on the reverse flow phenomenon is analyzed. Abstract: Under natural circulation, reverse flow may occur on the primary side of inverted U-tube steam generators (UTSGs). This phenomenon is significantly affected by the operating parameters of primary and secondary loops of the reactor and the design parameters of the steam generator. In this study, according to the design parameters of the UTSG in the Pressurized Water Reactor Parallel Channel Test Loop (PWR PACTAL), the reverse flow phenomenon in the primary side of U-tubes under the condition of flow decline is simulated by using the computational fluid dynamics (CFD) software FLUENT. Further, the effects of the inlet temperature and pressure at the primary loop, wall thickness, inner roughness, and thermal conductivity of U-tubes, feed water temperature, and flow rate of the secondary loop on the reverse flow phenomenon are investigated. The results show that the critical mass flow rate of the steam generator can be increased by increasing the temperature of the primary side, the operating pressure of the primary side, and the thermal conductivity of U-tubes, which boosts the flow reversal. The critical mass flow rate decreases and the reverse flow phenomenon is inhibited by increasing the mass flow rate and temperature of secondary side and the inner wall roughness of U-tubes. Further, changing the wall thickness of U-tubes has a negligible effect on the reverse flow phenomenon. Compared with the temperature of the secondary circuit, the temperature of the primary circuit has a more substantial effect on the reverse flow phenomenon. The conclusions can be used as reference for UTSG design and its operation under natural circulation.